Implementation of Differentiation Strategy in Teaching Procedure Texts in Grade VII at MTsS Thawalib Padang - Pasaribu, Salmiati Br; Tatalia, Ricci Gemarni; Fitri, Rahayu (International Journal of Educational Sciences and Development, 2025)
Purpose – This study aims to analyze the implementation of differentiated instruction strategies in teaching procedure texts in Grade VII at MTsS Thawalib Padang. The research focuses on the planning, implementation, and evaluation of this strategy in adapting learning to the diversity of students' learning styles, interests, and needs. Methodology/approach – This study employs a qualitative approach with a case study strategy. Data is collected through interviews, observations, and documentation from teachers and Grade VII students. Data analysis techniques include data reduction, data presentation, and validation using triangulation to ensure the accuracy of findings. Findings – The research findings indicate that the differentiated instruction strategy is effective in enhancing students' understanding and motivation toward procedure texts. In the planning stage, this strategy adapts learning to student diversity while integrating Islamic values, fostering an inclusive learning environment. During implementation, teachers apply differentiation in content, methods, and learning products using active techniques such as discussions, demonstrations, and skill-based projects. In the evaluation stage, a reflective approach with formative and summative assessments allows teachers to adjust instructional strategies based on student feedback.